How Widespread Were Private Investment and Regulatory Reform in Infrastructure Utilities During the 1990s? - Estache, Antonio; Goicoechea, Ana (World Bank, Washington, DC, 2012)
This note provides a snapshot as of 2004 of the share of countries with an independent regulatory agency and with at least some private sector financing of its sectoral investment needs for electricity, water and sanitation, and telecommunications. Among other things, they show that: For respectively, electricity, water and sanitation, and telecommunications, 51 percent, 21 percent, and 66 percent of the developing countries in the sample have an independent regulator, that is, an agency separate from a ministry and from the operator. For respectively, electricity generation, electricity distribution, water and sanitation, and telecommunications, 47 percent, 36 percent, 35 percent, and 59 percent of the developing countries in the sample have at least some private sector financing. The shares of both agencies and private sector involvement tend to increase with income levels. Latin and Central America and Eastern Europe are outliers among regions as almost systematically they have among the highest shares for both indicators across sectors (except water).